Curbing Traffic The Human Case for Fewer Cars in Our Lives. - Bruntlett, Chris (Island Press, 2021)
In 2019, mobility experts Melissa and Chris Bruntlett began a new adventure in Delft in the Netherlands. They had packed up their family in Vancouver, BC, and moved to Delft to experience the biking city as residents rather than as visitors. A year earlier they had become unofficial ambassadors for Dutch cities with the publication of their first book Building the Cycling City: The Dutch Blueprint for Urban Vitality. In Curbing Traffic: The Human Case for Fewer Cars in Our Lives, Melissa and Chris Bruntlett chronicle their experience living in the Netherlands and the benefits that result from treating cars as visitors rather than owners of the road. They weave their personal story with research and interviews with experts and Delft locals to help readers share the experience of living in a city designed for people. In the planning field, little attention is given to the effects that a "low-car" city can have on the human experience at a psychological and sociological level. Studies are beginning to surface that indicate the impact that external factors--such as sound--can have on our stress and anxiety levels. Or how the systematic dismantling of freedom and autonomy for children and the elderly to travel through their cities is causing isolation and dependency. In Curbing Traffic, the Bruntletts explain why these investments in improving the built environment are about more than just getting from place to place more easily and comfortably. The insights will help decision makers and advocates to better understand and communicate the human impacts of low-car cities: lower anxiety and stress, increased independence, social autonomy, inclusion, and improved mental and physical wellbeing. The book is organized around the benefits that result from thoughtfully curbing traffic, resulting in a city that is: child-friendly, connected, trusting, feminist, quiet, therapeutic, accessible, prosperous, resilient, and age-friendly. Planners, public officials, and citizen activists should have a greater understanding of the consequences that building for cars has had on communities (of all sizes). Curbing Traffic provides relatable, emotional, and personal reasons why it matters and inspiration for exporting the low-car city.